2019
DOI: 10.3390/cancers11070986
|View full text |Cite
|
Sign up to set email alerts
|

Morin Hydrate Reverses Cisplatin Resistance by Impairing PARP1/HMGB1-Dependent Autophagy in Hepatocellular Carcinoma

Abstract: Chemoresistance is a major obstacle that limits the benefits of cisplatin-based chemotherapy in various cancers, including hepatocellular carcinoma. De-regulation of the poly(ADP-ribose) polymerase 1 (PARP1)/high-mobility group box 1 (HMGB1) signaling pathway has been proposed as an important mechanism involved in cisplatin-resistance. In this study, we investigated therapeutic potential of a natural flavonoid Morin hydrate against cisplatin-induced toxicity using the HepG2DR multi-drug resistant cell line, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 44 publications
12
47
0
Order By: Relevance
“…Moreover, lymph node metastasis-positive gastric tumors have higher levels of RhoGDI2 expression than lymph node metastasis-negative tumors [80]. RhoGDI2 also protects gastric cancer cells from various chemotherapeutic agents, such as etoposide, staurosporine, and cisplatin, through upregulation of Bcl-2 expression [81,82]. Although RhoGDI1 is completely resistant to degradation during apoptosis, RhoGDI2 is well-characterized as a substrate for caspases and cleaved during apoptosis in various cells [72].…”
Section: Functions Of Rhogdis In Human Cancersmentioning
confidence: 99%
“…Moreover, lymph node metastasis-positive gastric tumors have higher levels of RhoGDI2 expression than lymph node metastasis-negative tumors [80]. RhoGDI2 also protects gastric cancer cells from various chemotherapeutic agents, such as etoposide, staurosporine, and cisplatin, through upregulation of Bcl-2 expression [81,82]. Although RhoGDI1 is completely resistant to degradation during apoptosis, RhoGDI2 is well-characterized as a substrate for caspases and cleaved during apoptosis in various cells [72].…”
Section: Functions Of Rhogdis In Human Cancersmentioning
confidence: 99%
“…Most studies have revealed that HMGB1 is an inducer for tumor cell autophagy and promotes tumor cell survival through autophagy [58][59][60][61]. Although the influence of autophagy on tumor cell survival has been well characterized, the link between MDSCs and autophagy remains poorly understood.…”
Section: Hmgb1 Affects Mdsc Survival Through Autophagymentioning
confidence: 99%
“…The presence of two aromatic rings connected by a c-pyrone ring, in which polar hydroxyl groups are bound at various positions to characterize the chemical structure of morin. All hydroxyl groups are responsible for the free radical-scavenging properties of flavonoids [18]. Morin has a promising anti-cancerous activity by reducing DNA damage and modulating signaling pathways responsible for proliferation and differentiation, which could lead to cell-cycle arrest and apoptosis [19,20].…”
Section: Epigenetic Modulation Of Emt: Natural Compounds As An Alternmentioning
confidence: 99%